Optimizing the Empowerment of BUMDes 'Pesaguan Mandiri' in Clean Water Provision to Improve the Health and Welfare of the Pesaguan Kanan Village Community - Salawati, Salawati; Budiasi, Yanti; Erion, Erion (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study aims to optimize the empowerment of BUMDes